Correction to: Genetic Diversity Among Genogroup II Noroviruses and Progressive Emergence of GII.17 in Wastewaters in Italy (2011–2016) Revealed by Next-Generation and Sanger Sequencing - E. Suffredini; M. Iaconelli; M. Equestre; B. Valdazo-González; A. R. Ciccaglione; C. Marcantonio; S. Della Libera; F. Bignami; G. La Rosa (Food and Environmental Virology, 2018)

Genetic Diversity Among Genogroup II Noroviruses and Progressive Emergence of GII.17 in Wastewaters in Italy (2011–2016) Revealed by Next-Generation and Sanger Sequencing - E. Suffredini; M. Iaconelli; M. Equestre; B. Valdazo-González; A. R. Ciccaglione; C. Marcantonio; S. Della Libera; F. Bignami; G. La Rosa (Food and Environmental Virology, 2018)

A Multidisciplinary Study of the DPRK Nuclear Tests - R. Carluccio; A. Giuntini; V. Materni; S. Chiappini; C. Bignami; F. D’Ajello Caracciolo; A. Pignatelli; S. Stramondo; R. Console; M. Chiappini (Pure and Applied Geophysics, 2014)

Fate of river Tiber discharge investigated through numerical simulation and satellite monitoring - R. Inghilesi; L. Ottolenghi; A. Orasi; C. Pizzi; F. Bignami; R. Santoleri (Ocean Science, 2012)
The aim of this study was to determine the dispersion of passive pollutants associated with the Tiber discharge into the Tyrrhenian Sea using numerical marine dispersion models and satellite data. Numerical results obtained in the simulation of realistic discharge episodes were compared with the corresponding evolution of the spatial distributions of MODIS diffuse light attenuation coefficient at 490 nm (K490), and the results were discussed with reference to the local climate and the seasonal sub-regional circulation regime. The numerical model used for the simulation of the sub-tidal circulation was a Mediterranean sub-regional scale implementation of the Princeton Ocean Model (POM), nested in the large-scale Mediterranean Forecasting System. The nesting method enabled the model to be applied to almost every area in the Mediterranean Sea and also to be used in seasons for which imposing climatological boundary conditions would have been questionable. Dynamical effects on coastal circulation and on water density due to the Tiber discharge were additionally accounted for in the oceanographic model by implementing the river estuary as a point source of a buoyant jet. A Lagrangian particle dispersion model fed with the POM current fields was then run in order to reproduce the effect of the turbulent transport of passive tracers mixed in the plume with the coastal flow. Two significant episodes of river discharge in both winter and summer conditions were discussed in this paper. It was found that the winter regime was characterized by the presence of a strong coastal jet flowing with the ambient current. In summer the prevailing wind regime induced coastal downwelling conditions, which tended to confine the riverine waters close to the shore. In such conditions sudden wind reversals due to local weather perturbations, causing moderate local upwelling, proved to be the only effective way to disperse the tracers offshore, moving the plume from the coast and detaching large pools of freshwater.

La vita e i pianeti: il mito e la scienza - Giovanni F. Bignami (Rendiconti Lincei. Scienze Fisiche e Naturali, 2004)